Minimum completion time for power-aware scheduling in cloud computing - Mehdi, Nawfal A.; Mamat, Ali; Aljuboori, Ali A.Alwan; Ziyad, Abdul-Mehdi (2012)
Reducing power consumption has been an essential requirement for Cloud resource providers not only to decrease operating costs, but also to improve the system reliability. This paper tackles the problem of minimizing power consuming in datacenters hosts and improving their load balancing simultaneously. Cloud computing based on the idea of offering services going to be executed on datacenters. These datacenters need huge amount of power if they are in the peak load or the tasks are not distributed efficiently in their machines. The paper presents an algorithm for task scheduling that lowering the power consuming and reducing the total datacenter load. An empirical study has been done to simulate the proposed algorithm, which is proved by the results.